The crystal bible : a definitive guide to crystals - Hall, Judy (Old Alresford : Godsfield ; Cincinnati, OH : Distributed to the trade markets in North America by Walking Stick Press, 2003)
...A comprehensive guide to crystals, their shapes, colors, and applications...
Includes index.
Keywords: Crystals; Bestimmungsbuch; Edelstein